2022
DOI: 10.7554/elife.79031
|View full text |Cite
|
Sign up to set email alerts
|

Experience-driven rate modulation is reinstated during hippocampal replay

Abstract: Replay, the sequential reactivation within a neuronal ensemble, is a central hippocampal mechanism postulated to drive memory processing. While both rate and place representations are used by hippocampal place cells to encode behavioral episodes, replay has been largely defined by only the latter – based on the fidelity of sequential activity across neighboring place fields. Here we show that dorsal CA1 place cells in rats can modulate their firing rate between replay events of two different contexts. This exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Because we were limited in the number of sessions that could be recorded from each animal, we used a fixed protocol with the rat always running more laps on track 1 compared to track 2, and with track 1 always being the first track used in the re-exposure. While it is possible that sleep replay rates increase with the recency of the behavioral episode to the sleep session (i.e., higher replay rates for track 2), previous replay data comparing replay between two novel tracks with a similar duration of experience suggests that this is not a significant effect 27 .…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Because we were limited in the number of sessions that could be recorded from each animal, we used a fixed protocol with the rat always running more laps on track 1 compared to track 2, and with track 1 always being the first track used in the re-exposure. While it is possible that sleep replay rates increase with the recency of the behavioral episode to the sleep session (i.e., higher replay rates for track 2), previous replay data comparing replay between two novel tracks with a similar duration of experience suggests that this is not a significant effect 27 .…”
Section: Resultsmentioning
confidence: 94%
“…Using chronically implanted microdrives 25 – 27 , we recorded from large ensembles of place cells during our behavioral task and the corresponding sleep sessions. We observed that place cells globally remapped between tracks 27 , 28 , while having similar place fields on the same track between RUN1 (first exposure) and RUN2 (re-exposure) (Fig. 2A, B and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations